On Filtration in a Rectangular Interchange with a particularly Unpermatable Vertical wall in the Evaporation - Bireslavskii, E.N.; Dudina, L.M. (Journal of Water, 2018)
We consider a plane steady-state filtration in a rectangular bridge with a partially impermeable vertical wall in the presence of evaporation from a free surface of groundwater. To study the effect of evaporation, a mixed multiparametric boundary-value problem of the theory of analytic functions is formulated and using the method of P. Y. Polubarinova-Kochina. Based on the proposed model, an algorithm is developed to calculate the dependence of efficiency and productivity of hydrodynamic analysis.
Keywords: Filtration; Evaporation; Groundwater; Free Surface; Polubarinova-Kochina Method; Conformal Mapping